Labor rights of tannery workers in Bangladesh: an overview - Mia, Md. Tuhin; Sarker, Md. Atiqur Rahman; Islam, Md. Zahidul (Kardan University, 2022)
Tannery in Bangladesh has long history as profitable business though it has both environmental and health hazards. Labor rights of tannery workers are disrupted and their standard of living is miserable. Nevertheless, the job of tannery workers is tedious. The aim of this paper is to explore the current status of basic labor rights maintained in tanneries based on Dhaka and Narayanganj districts of Bangladesh. This study is qualitative in nature. Primary data have been collected from tannery workers through four Focus Group Discussions (FGDs) and five observations from five different factory visits in 2021. The findings reveal that tannery workers are exploited by insufficient employment benefits and lack of welfare facilities as stated in BLA-2006. They also suffer from occupational health, hygiene and safety crisis. Long working hour and pay below minimum wage are also common in this sector. In addition, tannery workers have serious observation on their pay, leave, job security, maternity benefit etc. This paper concludes with the observations that basic labor rights at tanneries in Bangladesh are not protected, which generate grievances. This study also recommends for practicing BLA-2006 in tannery sector in order to avoid further legal obligation and possible labor unrest.